(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The purpose of the study was to find out the prominent variables contributing to shoppers decision for making a purchase. The subjects were 120 costumers, who had purchased different items from Archies shops located in Danik Bhasker Mall, Race Course Road, Gwalior, M. P.Twelve shopper’s decision making variables were selected for this study. They included (1) Emotions related to purchasing an item, (2) Cognition before making a purchase (3) Effect of service quality of sales team on purchase. The Factor Analysis (Principal Component Analysis) was done to find out the prominent shoppers decision making factors comprising of any one or all of the selected variables among costumers. The unloaded factors obtained were then rotated by Varimax method to find out the final solution. Item with loading greater than or equal to 0.70 of Varimax solution was selected for discussing each factor. Eight prominent factors extracted after factor analysis were cost, appearance, color, utility, good past memory, quality and friendly and knowledgeable sales teams in the respective shop.